Ingested Sharp Bone Fragment: An Unusual Cause of Acute Bowel Obstruction- Case Report - Raju Rangaswamy; Samit Kumar Badai; Sadyojata M Urugesan; Chabungbam Gyan Singh; Haobam Manihar Singh (Journal of Clinical and Diagnostic Research, 2016)
Acute bowel obstruction due to ingested foreign body (FB) like sharp bone fragment is a rare entity. As preoperative diagnosis was uncertain due to lack of proper history, diagnosis is usually done intraoperatively. Even though it is rare, we should consider it as differential diagnosis in patients with recent dietary history. Herein, we are reporting a 38-year-old man, without any psychiatric illness or previous surgery presenting to emergency department with the features of acute bowel obstruction. CT scan shows high density object in ileum suspicious of foreign body. Patient underwent exploratory laparatomy which reveals dilated small bowel with sharp bony object in ileum, which was retrieved with enterotomy.